نظرية الظروف الاستثنائية بين مقتضيات الحفاظ على النظام العام والتزام حماية الحقوق والحريات الأساسية - الفحلة, مديحة (revue mofakir; No 14 (2017): مجلـــة المفكــر, 2018)
This article treats the theory of exceptional circumstances by addressing its significance and presenting their definitions in law and sharia. In addition, we explain its historical source; knowing that many researchers relate its historical origin to the French council of state. Then, address to judicial control of administration works, because it is the most important guarantee of rights and freedoms. Especially, when applying this theory by the state which live in exceptional cases and disruption the functioning of institutions and threat system with insecurity.